Co-creation of Place-Based Content for Field Trips and Public Trails by Geo-Content Management - Kremer, Dominik; Wagner, Andreas (Transforming Places. Proceedings of the 4th International Symposium on Platial Information Science (PLATIAL’23), 2023)
While learning about places in classrooms takes large profit of digital geomedia, digital assisted learning on site is still bound to fragmented solutions, as innovative Extended Reality immersions often demand too much resources to be run on average smartphones. In addition, efforts staging digital aided learning experiences on site are still too cumbersome for regular teaching. In an explorative answer to this challenge, we introduce the FAU Geoexplorer, aiming at focussed presentation of geomedia on site supported by an easy to follow content creation process.<br
Keywords: location-based services; field-trips; geodidactics